Three Ways Forward to Improve Regional Information for Extreme Events: An Early Career Perspective - Langendijk, Gaby S.; Aubry-Wake, Caroline; Osman, Marisol; Gulizia, Carla; Attig-Bahar, Faten; Behrens, Erik; Bertoncini, André; Hart, Neil; Indasi, Victor S.; Innocenti, Silvia; van der Linden, Eveline C.; Mamnun, Nabir; et al. (Frontiers in Environmental Science, 2019)
This paper provides an early career researchers (ECRs) perspective on major challenges and opportunities that arise in the study and understanding of, and the provision of regional information for Climate, Weather and Hydrological (CWH) extreme events. This perspective emerged from the discussions of the early career three-day Young Earth System Scientists - Young Hydrologic Society (YESS-YHS) workshop, which was conjointly held with the Global Energy and Water Exchanges (GEWEX) Open Science Conference. In this paper we discuss three possible ways forward in the field: a stronger interaction between Earth system scientists and users, a collaborative modelling approach between the different modelling communities, and an increased use of unconventional data sources in scientific studies. This paper also demonstrates the important role of ECRs in embracing the above outlined pathways and addressing the long-standing challenges in the field. YESS and YHS networks encourage the global community to support and strengthen their involvement with ECR communities to advance the field of interdisciplinary Earth system science in the upcoming years to decades.